Development of Rice Stripe Tenuivirus Minireplicon Reverse Genetics Systems Suitable for Analyses of Viral Replication and Intercellular Movement - Zhang, Xiaoyan; Sun, Kai; Liang, Yan; Wang, Shuo; Wu, Kaili; Li, Zhenghe (Frontiers in Microbiology, 2021)
Rice stripe virus (RSV), a tenuivirus with four negative-sense/ambisense genome segments, is one of the most devastating viral pathogens affecting rice production in many Asian countries. Despite extensive research, our understanding of RSV infection cycles and pathogenesis has been severely impaired by the lack of reverse genetics tools. In this study, we have engineered RSV minireplicon (MR)/minigenome cassettes with reporter genes substituted for the viral open reading frames in the negative-sense RNA1 or the ambisense RNA2-4 segments. After delivery to Nicotiana benthamiana leaves via agroinfiltration, MR reporter gene expression was detected only when the codon-optimized large viral RNA polymerase protein (L) was co-expressed with the nucleocapsid (N) protein. MR activity was also critically dependent on the co-expressed viral suppressors of RNA silencing, but ectopic expression of the RSV-encoded NS3 silencing suppressor drastically decreased reporter gene expression. We also developed intercellular movement-competent MR systems with the movement protein expressed either in cis from an RNA4-based MR or in trans from a binary plasmid. Finally, we generated multi-component replicon systems by expressing the N and L proteins directly from complementary-sense RNA1 and RNA3 derivatives, which enhanced reporter gene expression, permitted autonomous replication and intercellular movement, and reduced the number of plasmids required for delivery. In summary, this work enables reverse genetics analyses of RSV replication, transcription, and cell-to-cell movement and provides a platform for engineering more complex recombinant systems.